Economical aspects concerning quality control of concrete - Skrzypczak, Izabela; Słowik, Marta (Budownictwo i Architektura, 2019)
The paper deals with economical aspects concerning the quality control of concrete. About 70% of total concrete production is connected with the structural concrete, the subject of quality control and/or conformity. When checking the conformity criteria for a compressive strength of concrete for a small number of samples, qualification errors do not affect the formation of costs associated with losses on external deficiencies. In order to avoid costs related to qualification errors and losses on external deficiencies, the number of samples should be set larger than the minimum (included in contract’s clauses). Furthermore, the designer recommendations should be indicated in the specification. In the paper the costs concerning quality control for concrete have been analyzed.